2019
DOI: 10.7717/peerj.7984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autogenous growth factors released from platelet concentrates on the osteogenic differentiation of periodontal ligament fibroblasts: a comparative study

Abstract: BackgroundPlatelet concentrates have been used in tissue regeneration. The purpose of this study was to examine effects of growth factors released from leukocyte- and platelet-rich fibrin (L-PRF) and concentrated growth factor (CGF) on the osteogenic differentiation of periodontal ligament fibroblasts (PDLFs).MethodsLeukocyte- and platelet-rich fibrins, CGFs and PDLFs were obtained from New Zealand rabbits. The release of basic fibroblast growth factor (bFGF), bone morphogenetic protein 2 (BMP-2) and transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Moreover, compared to PRF, previous studies showed a better regenerative capacity of CGF with no significant differences in mechanical and degradation properties [ 26 , 27 ]. Since it was reported that bFGF, BMP-2, and TGF-β1 were detected in rabbit-derived CGF and leukocyte- and platelet-rich fibrin (L-PRF) that could promote the proliferation and osteogenic differentiation of rabbit periodontal ligament fibroblasts in vitro [ 28 ], bone induction by the CGF alone graft was expected in the in vivo ectopic site. However, bone and cartilage induction did not occur alone in the CGF membrane, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared to PRF, previous studies showed a better regenerative capacity of CGF with no significant differences in mechanical and degradation properties [ 26 , 27 ]. Since it was reported that bFGF, BMP-2, and TGF-β1 were detected in rabbit-derived CGF and leukocyte- and platelet-rich fibrin (L-PRF) that could promote the proliferation and osteogenic differentiation of rabbit periodontal ligament fibroblasts in vitro [ 28 ], bone induction by the CGF alone graft was expected in the in vivo ectopic site. However, bone and cartilage induction did not occur alone in the CGF membrane, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit leukocyte- and PRF induced osteogenic differentiation in rabbit periodontal ligament cells 42 . In this regard, rabbit blood derived PRF significantly enhanced alkaline phosphatase enzymatic activity and osteogenic marker gene expression 42 .…”
Section: Discussionmentioning
confidence: 95%
“…Rabbit leukocyte- and PRF induced osteogenic differentiation in rabbit periodontal ligament cells 42 . In this regard, rabbit blood derived PRF significantly enhanced alkaline phosphatase enzymatic activity and osteogenic marker gene expression 42 . Correspondingly, human blood derived PRF significantly promoted alkaline phosphatase enzymatic activity and mineralization by human periodontal ligament cells 43 .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, CGF prolongs the duration of growth factor activity, which is suitable for growth factor synergy, enhancing cell proliferation and osteogenic differentiation. Some studies in vitro showed that CGF cocultured with periodontal ligament fibroblasts, and bone marrow stromal stem cells induce differentiation into osteoblasts [ 11 , 15 , 16 ]. In our study, no sufficient amount of new bone tissue was observed in the bone defect area filled with CGF alone, and there was no significant difference between CGF and the blank group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CGF and n-hydroxyapatite combination had the best osteogenic effect, which was superior to other groups regarding the amount of osteogenesis and reconstruction of the bone structure. This may be related to the following: n-hydroxyapatite provides a reliable scaffold for the attachment of early osteoblasts; CGF can release growth factors in the early postoperative period and promote the differentiation and proliferation of osteoblasts [ 16 ]. In the middle and later stages, CGF gel was absorbed into the bone particles, which resulted in more vascular tissue formation, enhanced local vascularization, increased nutrient supply, and growth factor regulation during bone repair and regeneration, resulting in more bone tissue formation.…”
Section: Discussionmentioning
confidence: 99%